Providing Advice to Job Seekers at Low Cost: An Experimental Study on Online Advice - Michèle Belot; Philipp Kircher; Paul Muller (Institute for the Study of Labor (IZA), 2016)
We develop and evaluate experimentally a novel tool that redesigns the job search process by providing tailored advice at low cost. We invited job seekers to our computer facilities for 12 consecutive weekly sessions to search for real jobs on our web interface. For half, instead of relying on their own search criteria, we use readily available labor market data to display relevant alternative occupations and associated jobs. This significantly broadens the set of jobs they consider and significantly increases their job interviews. Effects are strongest for participants who otherwise search narrowly and have been unemployed for a few months.
Keywords: D83; J62; C93; 330; online job search; occupational broadness; search design